In situ growth of SiC nanowires toughened preceramic resin-based adhesive for connecting Cf/C composites in extreme environments. Issue 16 (November 2020) - Wang, Mingchao; Zeng, Chen; Guo, Yanrui; Wei, Tong; Feng, Zhaojie; Zhang, Jingfang; Liu, Jiachen; Zhang, Haijun
Abstract: The heat-resistant adhesion technique for Cf /C composites was greatly improved through in situ growing SiC nanowires in a preceramic resin-based adhesive (NWsP). The introduction of ferrocene growth catalyst not only increased the strength and toughness of adhesive but also modified the interfacial connection effect between adhesive and carbon fibers. Under the synergy of bridging, stress-bearing, crack blocking and deflection, the room-temperature bonding strength of NWsP-adhesive after calcination at 1300 °C was increased to 20.2 MPa, while its high-temperature bonding strength at 1300 °C still kept above 15 MPa, and the relevant load-displacement curves showed up approximate yielding stages and dentate fracture modes. Besides, NWsP-adhesive could be directly used in extreme environments after curing without preheating, and its high-temperature bonding strength at 1300 °C reached 12.5 MPa, which brought great convenience to emergency repair.